YOUNG PERMANENT TEETH SEALANTS - Alina-Elena Adumitroaie; Mădălina Văcărașu-Andoni; Alina Georgiana Cobaschi; Carmen Savin; Ana-Elena Sîrghe; Daniel-Petru Cioloca; Andra-Claudia Tără; Vasilica Toma (Romanian Dental Association for Education, 2024)
Aim of the study This study aims to identify new concepts regarding young permanent teeth sealants used for caries prevention. Materials and methods Literature was searched for articles and written papers, using MeSH terms like: "young permanent teeth", "sealants". Results Dental sealing seems to be an effective solution in caries prevention, both in primary and young permanent teeth. Regarding the materials used as a sealant, literature shows three main categories: resin-based sealants, glass ionomer-based sealants and resin-modified glass ionomer sealants. Numerous studies have compared the efficacy of these types of sealants, concerning the stability of the material, retention rates and mechanical properties. Conclusions Dental sealing has proven to have a great efficacy in preventing occlusal caries and even arresting non-cavitary occlusal carious lesions in young permanent molars, regardless of the material used. Further clinical studies should be conducted, as current guidelines cannot clearly indicate a solution of choice regarding one material or other.